Determining the best hatch distances for selective laser melted SiC/Ti6Al4V(ELI) composites of different volume fractions of SiC - Masenate Thamae; Maina Maringa; Willie Bouwer du Preez (Results in Materials)
The goal of this research was to determine the best hatch distances for different SiC volume fractions of selective laser sintered SiC/Ti6Al4V(ELI) composites. The constituents of this composite have different thermal physical properties, which give rise to different melt characteristics of different SiC volume fractions. Non-overlapped tracks lead to debonding of the layers and the production of pores, which degrade the mechanical qualities of the final additively manufactured parts, whereas high overlap rates lead to inefficient use of material and long build times of parts. As a result, different hatch distances should be explored to determine the best overlap rate for each SiC volume fraction. To print single layers in the present work, different laser powers ranging from 100 W to 350 W and scanning speeds ranging from 0.3 m/s to 2.7 m/s were used. The single layers for each SiC volume fraction were built with different hatch distances of 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, and 110 μm. The parameters of laser power, scanning speed and therefore, linear energy density, as well as layer thickness, for each SiC volume fraction were kept constant. A cross-sectional analysis of the printed layers was performed with a scanning electron microscope to investigate the degree of overlapping of adjacent tracks, internal pores, and variation in the depth of penetration into the substrate in a single layer, while a top-surface analysis was performed to investigate surface roughness, surface interconnection of the adjacent tracks, and the formation of surface irregularities. The data collected and analysis carried out here yielded values of best hatch distances at SiC volume fractions ranging from 5 % to 25 %, while no best hatch distances were achieved at an SiC volume fraction of 30 %.